2021
DOI: 10.21270/archi.v10i8.5094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência das alterações sistêmicas dos pacientes atendidos pela Clínica de Odontologia do Centro Universitário Ruy Barbosa

Abstract: Complicações médicas, apesar de raras, podem ocorrer durante o atendimento odontológico, os pacientes portadores de alterações sistêmicas são os mais propensos a esta ocorrência, portanto requerem um atendimento especial pelo cirurgião-dentista. Objetivo: Avaliar o perfil das condições sistêmicas dos pacientes atendidos na clínica de Odontologia do Centro Universitário Ruy Barbosa. Metodologia: Foi realizado o levantamento dos pacientes atendidos na Clínica de Odontologia do Centro Universitário Ruy Barbosa - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…Anemia had a low prevalence and predominance in females compared to males, consistent with other studies 8,20 . Anemia is considered a contributing factor to the higher incidence of post-endodontic pain in females 34 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Anemia had a low prevalence and predominance in females compared to males, consistent with other studies 8,20 . Anemia is considered a contributing factor to the higher incidence of post-endodontic pain in females 34 .…”
Section: Discussionsupporting
confidence: 92%
“…A study 17 reported a similar rate of 56% for systemic alterations, aligning with the findings of the present study. Lower rates were found among the central Indian population seeking oral surgery care, with the following rates of systemic diseases: cardiovascular disease (35.57%), metabolic disorders (20.35%), hematological disorders (12.84%), and infectious diseases (3.55%) 8,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation